Cytogenetic profile and risk of transformation to acute myeloid leukemia (AML) in Indonesian patients with myelodysplastic syndrome (MDS): a pilot study [version 1; peer review: 2 approved] - Yuniar Harris Prayitno; Resti Mulya Sari; Veronika Juanita Maskito; Noorwati Sutandyo; Agus Susanto Kosasih; Ikhwan Rinaldi; Lyana Setiawan (F1000Research)
Background Cytogenetics is a fundamental examination in the course and management of myelodysplastic syndrome (MDS) since it is widely used as a diagnostic and prognostic indicator for the disease. Some cytogenetic profiles are associated with a higher risk of acute myeloid leukemia (AML) transformation. This is the first study to evaluate the cytogenetic profile of Indonesian patients with MDS. Methods This prospective cohort study was conducted at the Cancer Center and several other referral hospitals. Patients with primary MDS aged >18 years were included in the study. Clinical examination, peripheral blood smear, and bone marrow aspiration were performed, followed by cytogenetic examination. The results were further categorized into revised international prognostic scoring system (IPSS-R) scores, and cytogenetic profiles were descriptively presented. Patients were followed up for one year to evaluate AML transformation. Results A total of 28 MDS patients, aged 66±12 years, were included in this study. The majority of the patients were male (n=17;60.7%), aged 65 years or above (n=19;67.9%), diagnosed with MDS-MLD (n=14;50%), and had an intermediate cytogenetic group (n=4;14.3%). The IPSS-R score was high in 6 (21.4%) patients and very high risk in 3 (10.7%) patients. During one-year follow-up, AML transformation occurred in 3 (10.7%) patients, and 10 (35.7%) patients ceased. Monosomy 7 was observed in 6 (21.4%) patients but in one metaphase each. Deletion of chromosome 5 (del(5)(q31)), del (16)(q21.1), and del (16)(q11.2) were found in a male patient with MDS-EB1. Conclusions Monosomy 7 and deletion of chromosome 5 have been identified in Indonesian patients with MDS. MDS-EB has the highest risk of AML transformation.